technology proliferation and its impact on venezuelan family (Revista Electrónica REDINE, 2018)
The new information and communication technologies (ICT) have grown precipitously in the last five-year periods; where it has gone from computers with long and complicated instructions to your process and outcome, friendly and uncomplicated software for their operation. That is why the Venezuelan government has made great efforts to bring technology classes to groups of lower social strata through personal computers and tablets. In this sense, teachers are concerned about the academic performance of their students and the influence of these technologies on student performance style, and the use of such technologies in the work of teaching and learning.
Keywords: information and communication technologies (ICT); science and technology; education